2015
DOI: 10.1007/s12262-015-1301-0
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ultrasound-Guided Ilioinguinal/Iliohypogastric Nerve Block in Pediatric Same-Day Surgery

Abstract: The aim of this study was to evaluate the safety and efficacy of ultrasound-guided ilioinguinal/iliohypogastric nerve block (IINB) in pediatric patients undergoing sameday inguinal region surgery. Ninety patients aged 4-6 years, ASA levels I-II, were randomly divided into three groups: U, T, or C (n=30 each). After basic anesthesia, patients in group U underwent ultrasound-guided IINB, those in group T underwent traditional Schulte-Steinberg IINB, and those in group C (controls) received intravenous anesthesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…To the best of our knowledge, trisomy 18 and the sacrococcygeal dermal sinus were not associated. Although a recent meta-analysis revealed that quadratus lumborum and transversus abdominis plane blocks were more effective than other regional analgesia for pediatric inguinal hernia repair [ 13 ], ultrasound-guided IINB was also safe and effective [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, trisomy 18 and the sacrococcygeal dermal sinus were not associated. Although a recent meta-analysis revealed that quadratus lumborum and transversus abdominis plane blocks were more effective than other regional analgesia for pediatric inguinal hernia repair [ 13 ], ultrasound-guided IINB was also safe and effective [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lihua et al [13], on the other hand, found that ultrasound-guided ilioinguinal/iliohypogastric nerve block in pediatric one-day surgery causes decrease in heart rates and mean arterial pressure (MAP) compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…En un estudio de pacientes sometidos a cirugía ambulatoria de la región inguinal, se comparó el bloqueo II/IH bajo US, bloqueo II/IH bajo referencias anatómicas y grupo control con analgesia endovenosa sin bloqueo regional. El uso de bloqueo II/IH bajo US mejoró el efecto analgésico intraoperatorio, disminuyó la dosis requerida de AL, y se asoció a una recuperación post operatoria más rápida, (28).…”
Section: Bloqueo Ilio-inguinal-ilio-hipogástrico (Ii/ih)unclassified